2013
DOI: 10.1111/wej.12049
|View full text |Cite
|
Sign up to set email alerts
|

Improving sachet water quality – does Hazard Analysis and Critical Control Points apply?

Abstract: Sachet water is growing in importance as a source of drinking water for many people in Nigeria. In recent years, doubts over the quality of sachet water have grown. Commentators often cite poor distribution and storage practice for contamination of sachets. However, the integrity of the production process has been shown to be a weakness but has not received attention from the regulator or producers because of a lack of proper regulation of the industry. This study implemented the hazards analysis and critical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
0
4
0
1
Order By: Relevance
“…An Accra‐based study noted the presence of Pseudomonas aeruginosa in sachets in the absence of fecal contamination, suggesting that the bacteria was probably colonizing internal fittings of the filling machines and recontaminated the filtered water during production . This Pseudomonas finding signals a need for quality control to refocus on equipment maintenance and hygiene, an approach that may require technical and behavioral changes within the production process . With over six times Ghana's population, Nigeria has experienced slower industry maturation and greater regulatory challenges, and thus, we continue to see poor sachet quality reflected in Nigerian studies as demonstrated in a 2015 review of case reports primarily from Nigeria, but also including Ghana, India, and Egypt …”
Section: Product Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…An Accra‐based study noted the presence of Pseudomonas aeruginosa in sachets in the absence of fecal contamination, suggesting that the bacteria was probably colonizing internal fittings of the filling machines and recontaminated the filtered water during production . This Pseudomonas finding signals a need for quality control to refocus on equipment maintenance and hygiene, an approach that may require technical and behavioral changes within the production process . With over six times Ghana's population, Nigeria has experienced slower industry maturation and greater regulatory challenges, and thus, we continue to see poor sachet quality reflected in Nigerian studies as demonstrated in a 2015 review of case reports primarily from Nigeria, but also including Ghana, India, and Egypt …”
Section: Product Qualitymentioning
confidence: 99%
“…88 This Pseudomonas finding signals a need for quality control to refocus on equipment maintenance and hygiene, an approach that may require technical and behavioral changes within the production process. 148 With over six times Ghana's population, Nigeria has experienced slower industry maturation and greater regulatory challenges, and thus, we continue to see poor sachet quality reflected in Nigerian studies as demonstrated in a 2015 review of case reports primarily from Nigeria, but also including Ghana, India, and Egypt. 149 The overall picture yields several trends that have important implications for reducing water insecurity as sachet water continues to diffuse across Africa.…”
Section: Product Qualitymentioning
confidence: 99%
“…Each of the sub-processes consists of several elements (activities): the documentation development (design and technology, respectively); analysis of the developed documentation to meet the requirements in the field of product safety; expertise; approval of the document final version. The result of this phase implementation becomes the approved technical documentation, taking into account the safety requirements of both the product design and the technological equipment used in the production [11][12][13].…”
Section: ____________________________________________________________mentioning
confidence: 99%
“…Hopefully in the near future, more studies on this drinking water option in developing nations will emerge with design criteria that (i) pre-identifies core management issues to be addressed and (ii) seeks to answer specific questions vital to policy decision making (as attempted in the Hazard Analysis Critical Control Point study by Opatunji & Odhiambo, 2013). The envisioned future begins now.…”
mentioning
confidence: 97%